Effects of Avatar player-similarity and player-construction on gaming performance - Katherine M. Rahill; Marc M. Sebrechts (Computers in Human Behavior Reports, 2021)
There are a variety of ways in which the similarity of an avatar to its user has been achieved. In addition to the characteristics of an avatar, the source of the design can also impact the avatars utility. The current study focuses on how an avatar's similarity to the individual user through customization (similar vs. dissimilar) and who is the designer (player-vs other-construction) contribute to presence and performance. Results supported the separable importance of both avatar similarity and playerconstruction of avatars for game performance, as well as virtual presence, perception of performance, and perception of control. Performance was influenced by these design factors even in the absence of social engagement. Overall, the results of this study highlight the different effects that design, construction source and visual appearance have on avatar-player relationships and related performance.